2018
DOI: 10.1016/j.jnnfm.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the solvent viscosity on pure electro-osmotic flow of viscoelastic fluids

Abstract: In this work the fully-developed steady channel flow of the homogeneous polymer solution studied in [4] is revisited and a completely new analytical solution is proposed which is devoid of the limitations of the previous solution (3 2 ≤ 2∕27), i.e., it is valid for the complete range of the rheological parameters. The viscoelastic fluid is described by the simplified Phan-Thien and Tanner model with linear stress coefficient function for the polymer contribution plus a Newtonian solvent. The solution is also v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the channel central region, the shear and normal stresses are practically zero; the presence of both stresses is only close to the wall, being higher for lower De 2 sh for α = 0. Ferras et al [51] found the same behavior using the simplified Phan-Thien-Tanner model with a linear stress coefficient function for the polymer contribution plus a Newtonian solvent. For the codeformational time derivative (α = 0), both the shear and normal stresses are higher with increasing viscoelasticity.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…In the channel central region, the shear and normal stresses are practically zero; the presence of both stresses is only close to the wall, being higher for lower De 2 sh for α = 0. Ferras et al [51] found the same behavior using the simplified Phan-Thien-Tanner model with a linear stress coefficient function for the polymer contribution plus a Newtonian solvent. For the codeformational time derivative (α = 0), both the shear and normal stresses are higher with increasing viscoelasticity.…”
Section: Resultsmentioning
confidence: 66%
“…Afonso et al [23] obtained analytical solutions for the flow of viscoelastic fluids using the PTT model, They mentioned that theκ effects on the velocity profile is restricted to a narrow region, the effective EDL thickness: higher values ofκ lead to thinner EDL and consequently higher velocity gradients. The internal micro-structure of viscoelastic fluids interact in a complex process with electric fields and surfaces, leading either to adsorption or wall-depletion, as described in [51,57]. In Figure 7, the effect of the viscoelasticity on the dimensionless velocity withκ = 20 and Γ = 1 is exhibited.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientists have also explored different features of VEF flows for bioengineering applications using microfluidics devices. Various lab‐on‐chip microfluidic platforms have been developed for particle manipulation in VEF electroosmotic flow (EOF) within microchannels (Afonso, Alves, & Pinho, ; Ferrás, Cavadas, Resende, Afonso, & Pinho, ; Sadeghi, Saidi, & Mozafari, ) for micromixing of liquids as well as washing, stretching, sorting, focusing, and separation of particles of interest (D'Avino, Greco, & Maffettone, ; Gan, Lam, Nguyen, Tam, & Yang, ; Lu, Liu, Hu, & Xuan, ; Ramsay, Simmons, Ingram, & Stitt, ; Yuan et al ).…”
Section: Introductionmentioning
confidence: 99%